POST-TRAUMATIC ACTIVITY OF PHOSPHOMONOESTRASES IN THE TISSUES OF SCYLLA TRANQUEBARICA SUBJECTED TO AUTOTOMY AND BLEEDING STRESS - RAMALINGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Acid and alkaline phosphatases activity showed phasic changes in tissues of mud crab, Scylla tranquebarica to autotomy and bleeding stress. Being non-specific in action and in the selection of substrates their temporal changes suggest their role in meeting the energy demand. Their activities may also be attributed, besides energy derivation, to the mobilization of free nitrogenous substrates from the bound precursors and the maintenance of interior osmotic milieu in vivo. The overall changes in the tissues and the haemolymph in vivo represent preparatory events towards wound healing and regeneration involving both cellular and humoral factors.